Brazilian nurses' sociodemographic changes in the first decade of the 21st century - Gerson Luiz Marinho; Elisabete Pimenta Araújo Paz; Rafael Tavares Jomar; Ângela Maria Mendes Abreu (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: analyze income and work conditions of nurses in Brazil in 2000 and 2010. Methods: based on demographic census samples, socioeconomic characteristics of nurses were described according to income and work hours. Statistic models estimated the chances (odds ratios) of nurses having lower income despite working more than 40 hours per week. Results: the nurse population in Brazil grew at a rate of 12.5% per year. In the two study periods, approximately 11.0% of nurses received the lowest incomes and worked more than 40 hours per week. The most pronounced chances of belonging to this group were observed for those residing in the interior the South and Southeast regions of Brazil. They were also more elevated for nurses whose color/race was black or brown (pardo) and who lived with their parents. Conclusion and implications for the practice: the expressive increase in nurses occurred within the context of reduced socioeconomic inequalities. Less favorable work conditions were most evident for those classified as black and brown who lived in their parents' homes. We argue that the scenarios described may be related to the expansion of university educational institutions during the first decade of the twenty-first century, among other aspects.